An Overview of Use of Waste Plastic in Road Construction: Creating Sustainable and Durable Roads using Waste Plastic (Journal of Advances and Scholarly Researches in Allied Education, 2018)
–Disposal of waste plastic is major problem in India .waste plastic both commercial and industrial can be problem of disposal of waste plastic .Therefore it is necessary to utilize waste effectively with technical development day by in each field .Many of products are produced by using plastic waste . plastic waste consisting carry bags cups and other utilized plastic can be utilized plastics can be used as a coating over aggregate and this coated stone can be used for road construction.This economic method helps the pavements to resist higher temperature by reducing the making of cracks and reducing the rainwater infilteration which otherwise leads to development of potholes. Plastic roads would be boon for our country and near future we will have strong , durable, and ecofriendly roads which will relieve the earth from all type of plastic-waste this process is ecofriendly and economical too.